(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2019)
The lyttoniid brachiopods of the Permian exhibit a unique valve morphology: a branched lobate structure takes the form of the dorsal valve. In one group of lyttoniids, the genus Pirgulia, the ventral valve wraps around to form a cone that fully encloses the lobate structure. This has consequences for the dynamics of water flow and mode of life possible for these heteromorphic brachiopods. Here, we describe the skeletal microstructure and morphology of Pirgulia collected from the Upper Permian Sosio Limestone megablocks of Sicily and housed at the Yale Peabody Museum. We reconstruct the paleoecology of Pirgulia, characterizing it as semi-infaunal in soft sediment. By analogy to Richthofenia, the conical ventral valve and flapping dorsal valve functional morphology could have resisted fouling and assisted feeding in this environment. By comparison with the functional morphology of Pirgulia with other lyttoniids and richthofenids, we propose a revised mode of life for this genus, which involves adaptation to secondary soft-bottom substrates and support by sediment sticking. Despite constraints to the fundamental brachiopod body plan, modification of the valves in Pirgulia to achieve a conical morphology allowed it to inhabit a paleoecological niche distinct from that of other reef-building lyttoniids.